Subject Index (Journal of the American College of Cardiology, 2018)
Category Type Presentation Numbers Page Numbers ABSORB Bioresorbable Vascular Scaffold Studies Moderated Posters TCT 156-160 B67-B68 Acute and Long-Term CABG Results Moderated Posters TCT 205-209 B87-B88 Acute Kidney Injury During Percutaneous Interventions (PCI or TAVR) - I Moderated Posters TCT 126-130 B55-B56 Acute Kidney Injury During Percutaneous Interventions (PCI or TAVR) - II Moderated Posters TCT 592-596 B237-B239 Advanced FFR-Guided Decision Making Orals TCT 9-12 B4-B6 AMI Outcomes Orals TCT 21-24 B9-B11 Aortic Diseases and Intervention Moderated Posters TCT 285-289 B117-B119 ASD and PFO Closure - I Moderated Posters TCT 241-244 B100-B102 ASD and PFO Closure - II Moderated Posters TCT 552-555 B222-B223 ASD and PFO Closure - III Moderated Posters TCT 819-822 B326-B328 Assessment and Impact of Aortic Regurgitation Moderated Posters TCT 443-447 B178-B180 Best of Moderated Endovascular Intervention and Structural Heart Disease Posters Moderated Posters TCT 483-487 B193-B195 Best of Moderated PCI Poster Abstracts - I Moderated Posters TCT 166-170 B70-B73 Best of Moderated PCI Poster Abstracts - II Moderated Posters TCT 705-709 B282-B284 Best of Moderated TAVR Poster Abstracts - I Moderated Posters TCT 121-125 B53-B55 Best of Moderated TAVR Poster Abstracts - II Moderated Posters TCT 433-437 B174-B176 Bioresorbable Scaffolds vs Metallic Stents Moderated Posters TCT 310-314 B128-B129 Bioresorbable Vascular Scaffolds Orals TCT 61-64 B27-B28 Cardiogenic Shock and Hemodynamic Support Orals TCT 81-84 B36-B38 Cardiogenic Shock and Ventricular Assist - I Moderated Posters TCT 176-180 B75-B77 Cardiogenic Shock and Ventricular Assist - II Moderated Posters TCT 488-492 B195-B197 Cardiogenic Shock and Ventricular Assist - III Moderated Posters TCT 754-758 B301-B303 Carotid Stenting, Stroke Prevention, and Acute Stroke Intervention Moderated Posters TCT 210-215 B88-B90 Cath Lab of the Future: Strategies to Control Radiation Exposure - I Moderated Posters TCT 245-248 B102-B103 Cath Lab of the Future: Strategies to Control Radiation Exposure - II Moderated Posters TCT 556-559 B223-B224 Cath Lab of the Future: Strategies to Control Radiation Exposure - III Moderated Posters TCT 823-826 B328-B330 Cath Lab of the Future: Telemedicine and Robotics Moderated Posters TCT 438-442 B176-B178 Catheter-based Treatment of Peripheral Vascular Disease - I Moderated Posters TCT 131-135 B57-B58 Catheter-Based Treatment of Peripheral Vascular Disease - II Moderated Posters TCT 249-253 B103-B105 Catheter-based Treatment of Peripheral Vascular Disease - III Moderated Posters TCT 523-527 B211-B212 Cerebral Vascular Events in TAVR Patients Orals TCT 69-72 B30-B32 Chronic Pulmonary Embolism and Pulmonary Hypertension Moderated Posters TCT 161-165 B69-B70 Comorbidities in CAD - I Moderated Posters TCT 147-150 B63-B64 Comorbidities in CAD - II Moderated Posters TCT 612-616 B245-B247 Complex and Higher Risk Procedures for Indicated Patients (CHIP) Orals TCT 25-28 B11-B13 Complex TAVR Procedures Orals TCT 97-100 B42-B44 Computational Fluid Dynamics (CT-FFR, QFR, Intravascular Imaging-FFR, and Others) - I Moderated Posters TCT 305-309 B125-B127 Computational Fluid Dynamics (CT-FFR, QFR, Intravascular Imaging-FFR, and Others) - II Moderated Posters TCT 383-387 B155-B157 Computational Fluid Dynamics (CT-FFR, QFR, Intravascular Imaging-FFR, and Others) - III Moderated Posters TCT 578-582 B231-B233 Computational Fluid Dynamics (CT-FFR, QFR, Intravascular Imaging-FFR, and Others) - IV Moderated Posters TCT 617-621 B247-B249 Coronary Artery Surgery Orals TCT 105-108 B46-B47 Coronary Calcification - I Moderated Posters TCT 185-189 B79-B80 Coronary Calcification - II Moderated Posters TCT 652-656 B260-B262 Coronary Physiology in AMI Patients Moderated Posters TCT 870-874 B346-B348 Critical Limb Ischemia Moderated Posters TCT 364-368 B148-B149 CT-FFR. QFR, and OCT-FFR Orals TCT 37-40 B17-B18 CTO Follow-Up With Medical Therapy Moderated Posters TCT 528-531 B212-B214 CTO Intervention Orals TCT 77-80 B34-B36 DES Clinical Outomes Orals TCT 117-120 B50-B52 DES vs DES - I Moderated Posters TCT 195-199 B83-B84 DES vs DES - II Moderated Posters TCT 622-626 B249-B250 DES vs DES - III Moderated Posters TCT 662-666 B264-B266 EXCEL Trial Substudies Orals TCT 33-36 B15-B17 Heart Team Studies Moderated Posters TCT 359-363 B146-B147 Hemodynamic Support and High Risk PCI Moderated Posters TCT 448-452 B180-B182 Highest Peer-Reviewed Oral Abstracts of TCT 2018 - Sponsored by CCI and EuroIntervention Orals TCT 1-8 B1-B4 HOCM or Alcohol Septal Ablation Moderated Posters TCT 827-831 B330-B331 Hypertension and Renal Denervation Orals TCT 29-32 B13-B15 Intervention Therapies in Patients With Diabetes Mellitus - I Moderated Posters TCT 597-601 B239-B241 Intervention Therapies in Patients with Diabetes Mellitus - II Moderated Posters TCT 789-793 B314-B316 Interventional Treatment of Diseases of the Aorta Orals TCT 85-88 B38-B39 Intracoronary Physiology Studies - I Moderated Posters TCT 151-155 B64-B66 Intracoronary Physiology Studies - II Moderated Posters TCT 463-467 B186-B188 Intracoronary Physiology Studies - III Moderated Posters TCT 542-546 B218-B220 Intravascular Imaging Orals TCT 65-68 B28-B30 Intravascular Imaging and Incomplete Stent Apposition Moderated Posters TCT 503-507 B202-B204 Intravascular Imaging, PCI, and Long-Term Outcomes - I Moderated Posters TCT 190-194 B81-B82 Intravascular Imaging, PCI, and Long-Term Outcomes - II Moderated Posters TCT 423-427 B170-B172 Is There Still a Role for Bare Metal Stents? Moderated Posters TCT 270-274 B111-B113 Left Atrial Appendage Closure Moderated Posters TCT 200-204 B84-B86 Left Atrial Appendage Exclusion Orals TCT 101-104 B44-B45 LMCA Disease and Intervention - I Moderated Posters TCT 290-294 B119-B121 LMCA Disease and Intervention - II Moderated Posters TCT 329-333 B135-B136 LMCA Disease and Intervention - III Moderated Posters TCT 832-836 B331-B333 Long-Term DES studies Moderated Posters TCT 236-240 B98-B100 Lower Extremity Intervention Orals TCT 113-116 B49-B50 Machine Learning and Artificial Intelligence Moderated Posters TCT 231-235 B96-B98 Management of In-Stent Restenosis - I Moderated Posters TCT 339-343 B138-B140 Management of In-Stent Restenosis - II Moderated Posters TCT 458-462 B184-B186 Management of In-Stent Restenosis - III Moderated Posters TCT 574-577 B230-B231 Metallic Bioresorbable Vascular Scaffolds - I Moderated Posters TCT 349-353 B142-B144 Metallic Bioresorbable Vascular Scaffolds - II Moderated Posters TCT 700-704 B280-B282 MI Definitions Moderated Posters TCT 784-788 B313-B314 Minimalist Approach to TAVR - I Moderated Posters TCT 221-225 B92-B94 Minimalist Approach to TAVR - II Moderated Posters TCT 258-261 B107-B108 Miscellaneous PCI Techniques Moderated Posters TCT 254-257 B105-B106 Miscellaneous Pharmacotherapy Studies Moderated Posters TCT 725-728 B290-B291 Miscellaneous TAVR Complications - I Moderated Posters TCT 295-299 B121-B123 Miscellaneous TAVR Complications - II Moderated Posters TCT 532-536 B214-B216 MitraClip Studies Orals TCT 45-48 B20-B22 New Approaches to Ischemic or Dilated Cardiomypathy Moderated Posters TCT 744-748 B298-B299 New Intracoronary Physiology Techniques and Studies Orals TCT 93-96 B40-B42 New OCT Studies Moderated Posters TCT 266-269 B110-B111 New Polymeric Bioresorbable Vascular Scaffolds - I Moderated Posters TCT 388-392 B157-B159 New Polymeric Bioresorbable Vascular Scaffolds - II Moderated Posters TCT 428-432 B172-B174 New TAVR Devices Orals TCT 41-44 B18-B20 Newer DES - I Moderated Posters TCT 468-472 B188-B189 Newer DES - II Moderated Posters TCT 508-512 B204-B206 Newer DES - III Moderated Posters TCT 547-551 B220-B222 Newer DES - IV Moderated Posters TCT 583-586 B234-B235 Non-Atherosclerosis Coronary Artery Disease - I Moderated Posters TCT 398-402 B161-B162 Non-Atherosclerosis Coronary Artery Disease - II Moderated Posters TCT 632-636 B252-B254 Non-Elective TAVR or Balloon Valvuloplasty Moderated Posters TCT 570-573 B228-B229 Non-LM Bifurcation Intervention - I Moderated Posters TCT 216-220 B90-B92 Non-LM Bifurcation Intervention - II Moderated Posters TCT 408-412 B165-B166 Novel Structural Heart Disease Therapies Orals TCT 17-20 B8-B9 Obesity in CAD Moderated Posters TCT 418-422 B169-B170 Optical Coherence Tomography (OCT) Observations During Primary PCI in STEMI Moderated Posters TCT 344-348 B140-B142 Optimal Diagnosis and Treatment of Patients With STEMI or NSTEMI - I Moderated Posters TCT 378-382 B153-B155 Optimal Diagnosis and Treatment of Patients With STEMI or NSTEMI - II Moderated Posters TCT 498-502 B200-B202 Optimal Diagnosis and Treatment of Patients With STEMI or NSTEMI - III Moderated Posters TCT 804-808 B320-B322 Outcomes After PCI Treatment of CTO Lesions - I Moderated Posters TCT 683-685 B272-B273 Outcomes After PCI Treatment of CTO Lesions - II Moderated Posters TCT 715-718 B286-B287 PCI and Drug-Coated Balloons - I Moderated Posters TCT 226-230 B94-B96 PCI and Drug-Coated Balloons - II Moderated Posters TCT 262-265 B108-B109 PCI in High Bleeding Risk (HBR) Patients - I Moderated Posters TCT 300-304 B123-B125 PCI in High Bleeding Risk (HBR) Patients - II Moderated Posters TCT 537-541 B216-B218 PCI in High Bleeding Risk (HBR) Patients - III Moderated Posters TCT 841-845 B336-B337 PCI in Patients with Previous CABG Moderated Posters TCT 518-522 B208-B210 PCI in the Elderly - I Moderated Posters TCT 690-694 B275-B278 PCI in the Elderly - II Moderated Posters TCT 865-869 B345-B346 PCI Techniques and Outcomes Moderated Posters TCT 764-768 B305-B307 PCI Volumes and Outcomes - I Moderated Posters TCT 657-661 B262-B264 PCI Volumes and Outcomes - II Moderated Posters TCT 769-773 B307-B309 Percutaneous Interventions (PCI or TAV) in Dialysis Patients or Patients With Chronic Kidney Disease Moderated Posters TCT 637-641 B254-B256 Peri-Device Leaks Moderated Posters TCT 275-279 B113-B115 Pharmacology: Dual and Triple Anti-Platelet Therapy - I Moderated Post